2009
DOI: 10.1007/s12663-009-0078-8
|View full text |Cite
|
Sign up to set email alerts
|

Time lapse from the occurrence of trauma to the definitive management of mandibular fractures: a retrospective study

Abstract: The surgical management of maxillofacial trauma has come a long way in the last four millennia and without doubt will go further. The principles are not new but the interpretation constantly changes. A retrospective review of 52 inpatient records of mandibular fracture patients was done for the period 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…3 ). The data from 2 studies suggested that treatment delay was longer for patients with complications, 28 , 30 whereas 2 studies suggested a longer treatment delay for patients without complications. 27 , 29 The heterogeneity score was 83%, and therefore it was unreliable to pool mean treatment time by postoperative complications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ). The data from 2 studies suggested that treatment delay was longer for patients with complications, 28 , 30 whereas 2 studies suggested a longer treatment delay for patients without complications. 27 , 29 The heterogeneity score was 83%, and therefore it was unreliable to pool mean treatment time by postoperative complications.…”
Section: Resultsmentioning
confidence: 99%
“…There was variation among the types of mandible fracture included across studies with Spinelli et al 35 focusing on angle fractures only, Barker et al 29 excluding condylar and alveolar fractures, and 5 of 20 included studies not reporting mandible fracture location. 8 , 29 , 30 , 36 , 43 It is therefore difficult to compare complication rates between such studies, given that mandible fracture location is considered an important factor influencing the development of complications. 16 …”
Section: Discussionmentioning
confidence: 99%
“…The importance of patient compliance in the success of this protocol cannot be overemphasized. Lack of patient compliance has been implicated as one of the most definitive factor predisposing to postsurgical infections following maxillofacial trauma 21. A wide range of patient- and clinician-related factors influence the overall compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of patient compliance has been implicated as one of the most definitive factor predisposing to postsurgical infections following maxillofacial trauma. 21 A wide range of patient-and clinician-related factors influence the overall compliance. These include the socioeconomic status of the patient, oral hygiene, abusive habits, and forgetfulness.…”
Section: Discussionmentioning
confidence: 99%